How do food-derived satiety peptides regulate appetite? Insights into efficacy, assessment and mechanism - Ruiyang Yuan; Yuer Zhang; Yujia Lu; Yuchen Zhao; Xintong Yao; Rotimi E. Aluko; Na Zhang; Yuhao Zhang; Yu Fu (Trends in Food Science & Technology, 2026)

Laboratory to bench-scale performance evaluation of a biphasic solvent for low-concentration CO2 capture from simulated gas turbine flue gas - Hang Yu; Sining Kong; Wenrui Li; Yitao Gan; Lijian Jin; Ruiyang Gao; Fan Zhang; Linjun Yang (Chemical Engineering Journal, 2026)

MXene/LiFePO4 heterostructure for lithium recovery in flow-electrode capacitive deionization - Xinying Qiao; Ruiyang Ma; Haolin Li; Duo Yang; Xi Yu; Qian Yang; Zhichang Xiao; Xiaoxian Zhao; Shuaihua Zhang; Zhi Wang (Chemical Engineering Journal, 2026)

Waste heat recovery from flue gas inside MEA-based CO2 capture processes using heat pump technologies and associated environmental impact assessment - Lijian Jin; Debo Li; Lingxiao Zhan; Hang Yu; Wenrui Li; Yitao Gan; Sining Kong; Ruiyang Gao; Jinjin Li; Heng Chen; Linjun Yang (Journal of Cleaner Production, 2026)

Sustainable conversion of natural gas to high-value chemicals - Jie Qiu; Yuehan Cao; Changmin Tuo; Sibo Wang; Yong He; Xingran Zhao; Zhiyong Zou; Wang Yu; Yi Li; Heng Zheng; Dajun Wang; Zeai Huang; et al. (Gas Science and Engineering, 2026)

From energy-limited to substrate-limited: Machine learning reveals the spatially shifting controls on cirque morphology in high Mountain Asia - Jinrong Hu; Fuyuan An; Li Yan; Hongjun Yu; Longfei Gai; Xue Min; Ruiyang Xu (CATENA, 2026)

A novel Gemini extended surfactant for enhanced oil recovery in high-temperature high-salinity reservoirs - Yuxuan Zhang; Hengqian Jin; Hongjie Zhao; Kai Yu; Jinmao Sun; Yao Meng; Haoran Cheng; Ruiyang Zhao; Xingrong Zhang; Hongru Zhang (Chemical Engineering Journal, 2026)

Recent advances in cerium oxide redox cycle for solar thermochemical hydrogen production - Zilong Feng; Zeai Huang; Ruiyang Zhang; Shan Yu; Gang Feng; Decai Zhou; Guichuan Liu; Jiayi Liu; Ye Zhang; Jin Zhu; Jiarong Zhang; Yong He; et al. (Fuel, 2026)

Cropland evapotranspiration based on Sentinel-2 shortwave infrared data and ensemble Kalman filter - Lu Liu; Yunjun Yao; Qingxin Tang; Xueyi Zhang; Yufu Li; Joshua B. Fisher; Jiquan Chen; Jia Xu; Xiaotong Zhang; Ruiyang Yu; Zijing Xie; Jing Ning; et al. (Agricultural and Forest Meteorology, 2026)

Polyimine vitrimers as recyclable and rehealable matrices for solid-state luminescent carbon dots - Xiaoran Yang; Fanhao Zeng; Yu Duan; Ruiyang Li; Ziyuan Liu; Yuanke Xiang; Shuangbin Liu; Zhili Peng; Li Qiu (Chemical Engineering Journal, 2025)

Improving terrestrial evapotranspiration estimation of the Tibetan Plateau by coupling SEBS with machine learning-derived aerodynamic resistance - Yixi Kan; Huaiyong Shao; Yunjun Yao; Yufu Li; Xiaotong Zhang; Jia Xu; Xueyi Zhang; Zijing Xie; Jing Ning; Ruiyang Yu; Lu Liu; Jiahui Fan; et al. (Journal of Hydrology, 2025)

Study on the characteristics of vibration acoustic signals and rupture grading for reactor pipeline leaks - Xinyu Zhao; Zhuorun Zhang; Xiangpeng Du; Yu Wang; Jinchuan Yang; Zhangjun Feng; Ruiyang Zhong; Chuang Han; Jiaxin Mo; Jinlong Wan; Zhida Yang (Annals of Nuclear Energy, 2025)

MAT-MS: A mask-aware transformer for constructing gap-free MODIS normalized difference snow index products - Jiahui Xu; Ruiyang Hua; Shujie Wang; Stef Lhermitte; Qingyu Gu; Bailang Yu; Jianping Wu; Yan Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Construction of multilayer multifunctional hydrogel microspheres with natural macromolecules, tannic acid, and copper for enhanced diabetic wound healing - Zuhan Chen; Beizhi Jiang; Huanjing Bi; Chongfeng Wang; Yanyan Liu; Jingwen Wang; Ying Wang; Zejiaxin Niu; Ruiyang Ma; Boqing Dong; Xiaoyang Yu; Fang Xie; et al. (Chemical Engineering Journal, 2025)

Evaluation of two strategies from the SEBS model for estimating the daily terrestrial evapotranspiration values of the Tibetan Plateau - Yixi Kan; Huaiyong Shao; Yunjun Yao; Yufu Li; Xiaotong Zhang; Jia Xu; Xueyi Zhang; Zijing Xie; Jing Ning; Ruiyang Yu; Lu Liu; Jiahui Fan; et al. (Journal of Hydrology, 2025)

Natural Regeneration Enhances Long‐Term Soil Carbon Storage in Various Fractions More Effectively Than Active Restoration: Meta‐Analysis - Yuqian Ye; Ruiyang Zhang; Dashuan Tian; Jinsong Wang; Guirui Yu; Shuli Niu (Global Change Biology, 2025)
Restoration of terrestrial ecosystems, through both natural and active approaches, is critical for enhancing soil organic carbon (SOC) storage. However, the long‐term effects of these restoration approaches on soil aggregate organic carbon remain poorly understood. In this study, we conducted a global meta‐analysis to assess the temporal effects of natural and active restoration on SOC and aggregate organic carbon, including macroaggregate (MAC), microaggregate (MIC), and silt‐clay fraction (SCC) organic carbon. The overall global results showed that natural regeneration outperformed active restoration in enhancing SOC and MAC, with increases of 21% and 24%, respectively, higher than those of active restoration. Notably, the benefits of natural regeneration on SOC and MAC intensified over time, surpassing active restoration after 40 years. In different terrestrial ecosystems, natural regeneration showed greater effectiveness in late‐stage SOC and MAC accumulation, with 72% and 61% higher in forests (> 40 years) and 64% and 63% higher in grasslands (> 20 years) compared to active restoration. In shrublands, late‐stage (> 15 years) MIC accumulation was 62% higher under natural regeneration than under active restoration. In addition, natural regeneration enhanced SOC storage in deeper soil layers and in carbon‐poor areas. These findings highlight the long‐term superiority of natural regeneration for soil carbon sequestration, positioning it as a key strategy for sustainable ecosystem restoration and climate change mitigation.

EABC-AS: Elite-driven artificial bee colony algorithm with adaptive population scaling - Ruiyang Lin; Zesong Xu; Liyang Yu; Tongquan Wei (Swarm and Evolutionary Computation, 2025)

Magnetic field-induced electron spin polarization of Co-modified black phosphorus for enhanced electrocatalytic oxygen evolution performance - Taofen Wang; Hui Qiao; Zongyu Huang; Zhiwen Leng; Ruiyang Yu; Xi Chen; Rong Hu; Xiaohui Ren; Xiang Qi (Fuel, 2025)

Constructing an adverse outcome pathway framework for the impact of maternal exposure to PM2.5 on liver development and injury in offspring - Kexin Zhang; Li Tian; Qinglin Sun; Jianong Lv; Ruiyang Ding; Yang Yu; Yang Li; Junchao Duan (Environmental Toxicology and Pharmacology, 2024)

The dynamic trajectory of carbon dioxide removal from terrestrial ecosystem restoration: A critical review - Shuli Niu; Ruiyang Zhang; Song Wang; Yanan Wu; Weinan Chen; Dashuan Tian; Yuanyuan Huang; Jianyang Xia; Yunting Fang; Yangjian Zhang; Lingli Liu; Junhua Yan; et al. (Agricultural and Forest Meteorology, 2024)

Untargeted lipidomics uncover hepatic lipid signatures induced by long-term exposure to polystyrene microplastics in vivo - Yiming Ma; Yao Zeng; Mengqi Sun; Ruiyang Ding; Yang Yu; Junchao Duan (Toxicology Letters, 2024)

Integrative Metabolomics and Whole Transcriptome Sequencing Reveal Role for TREM2 in Metabolism Homeostasis in Alzheimer’s Disease - Meng Wang; Tao Wei; Chaoji Yu; Ruiyang Li; Yunsi Yin; Hanchen Yang; Run Di; Xinyi Xia; Qi Qin; Yi Tang (Molecular Neurobiology, 2024)

Optimization of Ti-PA efficiently catalytic the alcoholysis of waste PET using response surface methodology - Ruiyang Wen; Guoliang Shen; Yang Yu; Jing Zhu; Shijie Xu; Jie Wei; Yue Huo (Environmental Science and Pollution Research, 2024)

Multimodel ensemble estimation of Landsat-like global terrestrial latent heat flux using a generalized deep CNN-LSTM integration algorithm - Xiaozheng Guo; Yunjun Yao; Qingxin Tang; Shunlin Liang; Changliang Shao; Joshua B. Fisher; Jiquan Chen; Kun Jia; Xiaotong Zhang; Ke Shang; Junming Yang; Ruiyang Yu; et al. (Agricultural and Forest Meteorology, 2024)

Size-dependent toxicity of polystyrene microplastics on the gastrointestinal tract: Oxidative stress related-DNA damage and potential carcinogenicity - Ruiyang Ding; Yueyue Chen; Xuemin Shi; Yang Li; Yang Yu; Zhiwei Sun; Junchao Duan (Science of The Total Environment, 2024)

Evaluation of seven satellite-based and two reanalysis global terrestrial evapotranspiration products - Zijing Xie; Yunjun Yao; Qingxin Tang; Meng Liu; Joshua B. Fisher; Jiquan Chen; Xiaotong Zhang; Kun Jia; Yufu Li; Ke Shang; Bo Jiang; Junming Yang; et al. (Journal of Hydrology, 2024)

Full-scale upgrade activated sludge to continuous-flow aerobic granular sludge: Implementing microaerobic-aerobic configuration with internal separators - Cheng Yu; Kaijun Wang; Kaiyuan Zhang; Ruiyang Liu; Pingping Zheng (Water Research, 2024)

Characterization of pollen tube development in distant hybridization of Chinese cork oak (Quercus variabilis L.) - Meng Ke; Huayu Si; Yongliang Qi; Yuhan Sun; Yousry A. El-Kassaby; Zhiyong Wu; Shian Li; Kelin Liu; Hai Yu; Ruiyang Hu; Yun Li (Planta, 2023)

Soil moisture at 30 m from multiple satellite datasets fused by random forest - Jing Ning; Yunjun Yao; Qingxin Tang; Yufu Li; Joshua B. Fisher; Xiaotong Zhang; Kun Jia; Jia Xu; Ke Shang; Junming Yang; Ruiyang Yu; Lu Liu; et al. (Journal of Hydrology, 2023)

Coupling a light use efficiency model with a machine learning-based water constraint for predicting grassland gross primary production - Ruiyang Yu; Yunjun Yao; Qingxin Tang; Changliang Shao; Joshua B. Fisher; Jiquan Chen; Kun Jia; Xiaotong Zhang; Yufu Li; Ke Shang; Junming Yang; Lu Liu; et al. (Agricultural and Forest Meteorology, 2023)

Coupling physical constraints with machine learning for satellite-derived evapotranspiration of the Tibetan Plateau - Ke Shang; Yunjun Yao; Zhenhua Di; Kun Jia; Xiaotong Zhang; Joshua B. Fisher; Jiquan Chen; Xiaozheng Guo; Junming Yang; Ruiyang Yu; Zijing Xie; Lu Liu; et al. (Remote Sensing of Environment, 2023)

Highly efficient conversion of phenol to cyclohexanone on Pd-based catalysts by cobalt doping - Defu Yin; Renjie Ji; Fanglin Lv; Long Jiang; Jingyun Zhang; Mingya Liu; Zhen Jia; Shitao Yu; Ruiyang Zhao; Yue Liu (Fuel, 2023)

Biodiversity alleviates the decrease of grassland multifunctionality under grazing disturbance: A global meta‐analysis - Ruiyang Zhang; Dashuan Tian; Han Y. H. Chen; Eric W. Seabloom; Guodong Han; Shaopeng Wang; Guirui Yu; Zhaolei Li; Shuli Niu (Global Ecology and Biogeography, 2022)
Aim Biodiversity drives the delivery of multiple ecosystem functions related to carbon and nutrient cycling (ecosystem multifunctionality, EMF), and biodiversity and ecosystem functioning are strongly threatened by intensive grazing in grasslands. However, it remains unclear how biodiversity regulates EMF changes in response to intensive grazing. Location Global. Time period From 1992 to 2018. Major taxa studied Grassland. Methods Here, we conducted a global synthesis using 373 paired observations from 90 published studies to address the responses of plant diversity, EMF and their relationships to grazing disturbance depending on grazing intensity, livestock type, grazing duration, and climatic aridity. Results Our results showed that EMF significantly decreased with increasing grazing intensity, but the negative EMF response was alleviated at high levels of plant diversity. The grazing‐induced changes in EMF increased linearly with the changes in plant diversity, with the slopes increasing by 78.9% from light to heavy grazing. In addition, the grazing‐induced decrease of EMF was stronger with longer grazing duration and more arid climates. Structural equation models suggested that grazing intensity reduced EMF largely via decreasing plant diversity, whereas upsizing livestock type promoted EMF by increasing plant diversity. Main conclusions This study highlights the key role of biodiversity in mediating EMF in response to intensifying grazing disturbance. We call for conservation of biodiversity to maintain grassland multifunctionality and services.

Inversion reflectance by apple tree canopy ground and unmanned aerial vehicle integrated remote sensing data - Ruiyang Yu; Xicun Zhu; Xueyuan Bai; Zhongyu Tian; Yuanmao Jiang; Guijun Yang (Journal of Plant Research, 2021)

Estimation of Nitrogen Content on Apple Tree Canopy through Red-Edge Parameters from Fractional-Order Differential Operators using Hyperspectral Reflectance - Yufeng Peng; Xicun Zhu; Jingling Xiong; Ruiyang Yu; Tianlin Liu; Yuanmao Jiang; Guijun Yang (Journal of the Indian Society of Remote Sensing, 2021)

Micromotion of implant-abutment interfaces (IAI) after loading: correlation of finite element analysis with in vitro performances - Zhi Li; Shanshan Gao; Hongyu Chen; Ruiyang Ma; Tingting Wu; Haiyang Yu (Medical & Biological Engineering & Computing, 2019)

Removal of nitrogen from wastewaters by anaerobic ammonium oxidation (ANAMMOX) using granules in upflow reactors - Chong-Jian Tang; Cheng-Shan Duan; Cheng Yu; Yu-Xia Song; Li-Yuan Chai; Ruiyang Xiao; Zongsu Wei; Xiao-Bo Min (Environmental Chemistry Letters, 2017)

A Comparative Analysis of the atp8 Gene Between a Cytoplasmic Male Sterile Line and Its Maintainer and Further Development of a Molecular Marker Specific to Male Sterile Cytoplasm in Kenaf (Hibiscus cannabinus L.) - Xiaofang Liao; Yanhong Zhao; Peng Chen; Bujin Zhou; Yong Diao; Mingli Yu; Zhipeng Huang; Ruiyang Zhou (Plant Molecular Biology Reporter, 2016)